As estruturas simbólicas e as relações de poder que perpassam a juventude em comunidades rurais: um estudo de caso em Bebida Velha - Pureza/RN - Silva Júnior, Marcos Aurélio Freire da (2020)
When it comes to the concept of youth, two simplistic conceptions permeated the popular imaginary for a long time. One of them was the idea of the young person as a problematic individual or one who causes social disorder, and the other was that of the urban young person and student of the middle class. Both conceptions are anchored in the idea of the young person as an "adult in process", thus limiting the analytical capacity of the category. Over time, youth as a category has gained academic relevance because it has been an important actor in the country's social and political life. This process has consolidated in academia and in the State - through public policies - young people as political actors (VÁZQUEZ, 2015). In this sense, rural youth reflects a heterogeneous category that presents a series of possibilities for studies and analysis, given the particularities that permeate it. However, the researches that are dedicated to analyzing young people in the countryside are very focused on themes such as the insertion of young people in agricultural production or the dilemma between staying and leaving the rural environment. This present work seeks to contribute to the ongoing advances in the literature on rural youth seeking to relate the category with symbolic power relations (BOURDIEU, 1989), in an attempt to understand how power relations and symbolic domination are present in the lives of rural youth in Bebida Velha, a community located in Pureza/RN. We will use here the theoretical framework on power, habitus, and field, present in the works of Pierre Bourdieu. For this, we will use as analytical methodology the Discourse of the Collective Subject, which consists of a technique with a qualitative bias idealized by Fernando Lefevre and Ana Maria Lefevre and which aims to build a collective discourse based on individual discourses of the same category or social group. Collective discourses relate to values, knowledge, and practices that direct behaviors and social relationships, which are expressed through feelings, attitudes, words and expressions (LEFEVRE; LEFEVRE, 2014). From the analysis of the Discourse of the Collective Subject, built through 15 interviews conducted with young people, we realize that the main spaces of socialization of rural youth can be reproducers of the symbolic relationships of power and domination, while representing spaces of coexistence and opportunities. In this way, the Discourse of the Collective Subject made possible an analysis of the relations that the rural youth have with education, work, family and groups of participation and leisure and how they face the barriers found in these fields. The results obtained here offer a wide possibility of future research on power relations, discourses, trajectories, and narratives of rural youth.